Doctor Foster. Season two [videorecording (DVD)] - Jones, Suranne, 1978-; Carvel, Bertie, 1977-; Ashitey, Clare-Hope, 1987- (BBC Worldwide Americas, Inc., 2018)
Two years after the events of season one, Dr. Gemma Foster's husband Simon returns and brings unwelcome complications and instability to Gemma's life and that of her teenage son Tom.